The reasoning state / Edward Stiglitz, Cornell University. - Stiglitz, Edward H., 1980- (Cambridge University Press, 2022)
Administrative bodies, not legislatures, are the primary lawmakers in our society. This book develops a theory to explain this fact based on the concept of trust. Drawing upon Law, History and Social Science, Edward H. Stiglitz argues that a fundamental problem of trust pervades representative institutions in complex societies. Due to information problems that inhere to complex societies, the public often questions whether the legislature is acting on their behalf-or is instead acting on the behalf of narrow, well-resourced concerns. Administrative bodies, as constrained by administrative law, promise procedural regularity and relief from aspects of these information problems. This book addresses fundamental questions of why our political system takes the form that it does, and why administrative bodies proliferated in the Progressive Era. Using novel experiments, it empirically supports this theory and demonstrates how this vision of the state clarifies prevailing legal and policy debates.